Current Status of Plastic Waste and Proposing Solutions to Raise Community Awareness in Reducing Plastic Waste in Vietnam - Tuat Nguyen Thi Nham (Engineering And Technology Journal, 2024)
Research results showed that plastic waste in Vietnam arises from many different sources; The total amount of plastic waste in Vietnam is 3.27 million tons/year, accounting for about 8-12% of household solid waste and about 5% of medical waste; The treatment and recycling of plastic waste is still limited, up to 90% of plastic waste is burned, buried or discharged into the environment, only about 10% of plastic waste is recycled. To reduce plastic waste, it is necessary to raise awareness and and community responsibility in the production, distribution, use of plastic products and in the collection and classification, recycling and treatment of plastic waste. Propaganda solutions need to be implemented in many different forms, suitable for each audience. Propaganda activities must have long-term, clear, focused, and scripted strategies and campaigns to orient the community and help the community understand the harmful effects of plastic and microplastic waste, thereby changing consumption habits (refuse and minimize the use of plastic bags and single-use plastic products at the workplace and in entertainment services, restaurants, hotels, markets, supermarkets, conferences, seminars, meetings and holidays, anniversaries and other events); Encourage the use of recycled, environmentally friendly products to replace toxic plastic products.